PERKIRAAN PENJUALAN KOPI RAJA DI CV. MAHKOTA JAYA ABADI PADANGSIDIMPUAN PERIODE JANUARI 2017 - DESEMBER 2017 - evy cahyani, utari; Aziz Siregar, Fatahuddin (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Coffee sales of King CV. Mahkota Jaya Abadi Padangsidimpuan often goes up and down abnormally so it experiences problems, so the purpose of this study is to find out the estimated sales of coffee king on CV. Mahkota Jaya Abadi Padangsidimpuan for the January 2017 period to December 2017. The method used is the time series method consisting of linear trend methods, parabolic trend methods, exponential trend methods, quadratic trend methods and semi-average methods. A better method is used to determine the estimated sales of king coffee on CV. Mahkota Jaya Abadi Padangsidimpuan is a Parabolic Trend method with the equation: Y = 2,528,625 + 34,6x + 15,42x2, this equation has the smallest MSE of 161,632,1896. From the equation, it can be seen that the estimated values for the period January 2017 to December 2017 are: January 2017 amounting to 5,584 boxes, February 2017 amounting to 6,517 boxes, March 2017 amounting to 7,573 boxes, April 2017 amounting to 8,753 boxes, May 2017 amounting to 10,056 boxes, June 2017 11,482 box, July 2107 amounted to 13,031 boxes, August 2017 amounted to 14,704 boxes, September 2017 amounted to 15,497 boxes, October 2017 amounted to 18,420 boxes, November 2017 amounted to 20,463 boxes and December 2017 amounted to 22,630 boxes.Keywords: Planning and Sales Estimates